Development of procedure for assessing the degree of enviromental hazard from the sources of aquatic environment pollution - Magas, Nataliya; Trokhymenko, Ganna; Blahodatnyi, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2018)
The new procedure for evaluation of the degree of environmental safety of water sites based on the comparison of the influence of separate point sources of sewage discharge was developed. The use of this procedure will make it possible to solve the problem of identifying ecologically dangerous sites and to determine priority directions of aquatic sites protection in the region. The essence of this procedure is to assess the environmental hazard of specific facilities of the national economy taking into account the safety level, the degree of influence on the water quality of an aquatic site, effectiveness of monitoring and the magnitude of anthropogenic load. The logical-mathematical model of evaluating the impact of sources of water environment pollution, based on determining the coefficients of conditions of sewage discharge, sewage pollution and the load on an aquatic site, was proposed. The degree of environmental hazard of the sources of pollution of aquatic sites was determined by the value of coefficient of harmful influence of a pollution source on aquatic sites by the five-level scale from "safe" to "extremely hazardous". The designed scale corresponds to the environmental classification of the Water Framework Directive of the EU 2000/60/EU. Testing of the developed procedure was performed on an example of the section of a river basin that is typical for territorial production complexes, where the facilities of nuclear power industry, industrial manufacturing and public utilities are located. Based on determining block and total coefficient of harmful influence of the sources of pollution of aquatic sites, we developed the map of ecological hazard of the sources of the river basin pollution. The sources of pollution of aquatic sites were classified by the designed scale. It was established that large enterprises of housing and communal services and the facilities of machine-building industry have the greatest degree of environmental hazard. These facilities belong to class II and are described as "hazardous’. Enterprises of atomic power and hydropower plants belong to class III of hazard − "moderately hazardous". Results of the analysis can be used to develop water resources management strategies and measures to reduce the impact of pollution sources on aquatic sites